Cytotoxic and In Silico Evaluation of Hyrtios erectus Extract Against T47D Breast Cancer Cells: A Potential Marine-Derived Anticancer Agent (Journal of Fundamental and Applied Pharmaceutical Science, 2025)
Hyrtios erectus is a marine sponge species with promising potential as an anticancer agent. This study aimed to evaluate the cytotoxic activity of Hyrtios erectus extract against T47D breast cancer cells and assess the drug-likeness of its active compounds through in silico approaches. The investigation began with a phytochemical screening of the extract, followed by a cytotoxicity assay using the MTT method. The in silico analysis included PASS prediction, ADMET evaluation, and molecular docking. Phytochemical screening revealed the presence of flavonoids, alkaloids, terpenes, and saponins. The cytotoxicity test yielded an IC₅₀ value of 12.73 ± 1.05 µg/mL and a selectivity index (SI) of 18.16, indicating strong cytotoxic activity and high selectivity towards T47D breast cancer cells. PASS and ADMET analyses predicted that 20 identified compounds possess anticancer potential with low toxicity. Molecular docking results exhibited favorable binding energies for 2-chloro-6-phenyl-8H-quinazolino[4,3-b]-quinazolin-8-one, Echinoclerodane A, and 5-hydroxy-1H-indole-3-carboxylic-acid-methyl-ester, suggesting significant interaction with cancer-related protein targets. These findings support the potential of Hyrtios erectus extract and its bioactive compounds as promising candidates for anticancer drug development.